Pengaruh Brand Awareness, Perceived Quality, dan Brand Image terhadap Brand Loyalty pada Generasi Y di Indonesia - Fajariah, Nuraidya; Thoyib, Armanu; Rahman, Fatchur (Jurnal Aplikasi Manajemen, 2016)
Brand is an important factor that can attract the purchasing interest of Generation Y. This study aimed to examine the effect of brand awareness, perceived quality, and brand image to brand loyalty of Generation Y (15 to 33 years old). Increased purchasing power of generation Y are anticipated to make them become important targets for the brand. The samples of this study were 160 respondents of Generation Y and analyzed with path analysis. The result indicated that brand awareness and perceived quality were positive significantly affected to brand image and brand loyalty. Brand image positive significantlyaffected to brand loyalty. Brand image was able tomediated properly theeffect between brand awareness and perceived quality on brand loyalty.